Extracellular Vesicles Improve Post‐Stroke Neuroregeneration and Prevent Postischemic Immunosuppression. (3rd September 2015) - Doeppner, Thorsten R.; Herz, Josephine; Görgens, André; Schlechter, Jana; Ludwig, Anna-Kristin; Radtke, Stefan; de Miroschedji, Kyra; Horn, Peter A.; Giebel, Bernd; Hermann, Dirk M.
Abstract : The effects of mesenchymal stem cell (MSC)‐derived extracellular vesicles were compared with those of MSCs i.v. delivered 1, 3, and 5 days or 1 day after focal cerebral ischemia in mice. Motor coordination deficits, brain injury, immune responses in peripheral blood and brain, and cerebral angiogenesis and neurogenesis were analyzed. Postischemic immunosuppression was attenuated in peripheral blood 6 days after ischemia, providing an appropriate external milieu for successful brain remodeling. Abstract : Although the initial concepts of stem cell therapy aimed at replacing lost tissue, more recent evidence has suggested that stem and progenitor cells alike promote postischemic neurological recovery by secreted factors that restore the injured brain's capacity to reshape. Specifically, extracellular vesicles (EVs) derived from stem cells such as exosomes have recently been suggested to mediate restorative stem cell effects. In order to define whether EVs indeed improve postischemic neurological impairment and brain remodeling, we systematically compared the effects of mesenchymal stem cell (MSC)‐derived EVs (MSC‐EVs) with MSCs that were i.v. delivered to mice on days 1, 3, and 5 (MSC‐EVs) or on day 1 (MSCs) after focal cerebral ischemia in C57BL6 mice. For as long as 28 days after stroke, motor coordination deficits, histological brain injury, immune responses in the peripheral blood and brain, and cerebral angiogenesis and neurogenesis were analyzed. Improved neurological impairment and long‐term neuroprotection associated with enhanced angioneurogenesis were noticed in stroke mice receiving EVs from two different bone marrow‐derived MSC lineages. MSC‐EV administration closely resembled responses to MSCs and persisted throughout the observation period. Although cerebral immune cell infiltration was not affected by MSC‐EVs, postischemic immunosuppression (i.e., B‐cell, natural killer cell, and T‐cell lymphopenia) was attenuated in the peripheral blood at 6 days after ischemia, providing an appropriate external milieu for successful brain remodeling. Because MSC‐EVs have recently been shown to be apparently safe in humans, the present study provides clinically relevant evidence warranting rapid proof‐of‐concept studies in stroke patients. Significance: Transplantation of mesenchymal stem cells (MSCs) offers an interesting adjuvant approach next to thrombolysis for treatment of ischemic stroke. However, MSCs are not integrated into residing neural networks but act indirectly, inducing neuroprotection and promoting neuroregeneration. Although the mechanisms by which MSCs act are still elusive, recent evidence has suggested that extracellular vesicles (EVs) might be responsible for MSC‐induced effects under physiological and pathological conditions. The present study has demonstrated that EVs are not inferior to MSCs in a rodent stroke model. EVs induce long‐term neuroprotection, promote neuroregeneration and neurological recovery, and modulate peripheral post‐stroke immune responses. Also, because EVs are well‐tolerated in humans, as previously reported, the administration of EVs under clinical settings might set the path for a novel and innovative therapeutic stroke concept without the putative side effects attached to stem cell transplantation.